The Entrepreneurs Productivity Performance During COVID-19 In PPR Hiliran Ampang - Nur Alia Emira, Zulkifli (Universiti Malaysia Sarawak (UNIMAS), 2021)
The discovery of COVID-19 that spread all around the world have led many governments to take drastic measures. The movement control order and the lockdown of large parts of society and economic life has shocked many economic actors including SMEs as the largest contributor to GDP in Malaysia. The existence of COVID-19 and the new normal directed by the government to all sectors has presented new challenges to entrepreneurs to operate businesses. Since the issues received by entrepreneurs during pandemic are unforeseen problems, entrepreneurs take various business operations management measures. The challenges received during the pandemic have developed the potential of entrepreneurs to be into the context of human development. The purpose of this study is to learn the entrepreneur’s productivity performance during COVID-19 in PPR Hiliran Ampang. This study was carried out by using qualitative methods to explore the impact received by entrepreneurs as well as action to restrategize the business. Entrepreneur’s skills in changing environment are also discussed in this study by interviewing five (5) entrepreneurs who actively conducted SMEs during the pandemic. All informants from PPR Hiliran Ampang were selected by using purposive sampling. The data obtained from the interview sessions were analysed through transcribe data analysis.